2021
DOI: 10.1007/s41347-021-00204-8
|View full text |Cite
|
Sign up to set email alerts
|

WeCareAdvisor, an Online Platform to Help Family Caregivers Manage Dementia-Related Behavioral Symptoms: an Efficacy Trial in the Time of COVID-19

Abstract: Dementia-related behavioral and psychology symptoms (BPSD) are undertreated and have negative consequences. However, families do not have access to disease information, tailored problem-solving  and effective management strategies, and with COVID-19, are more socially isolated and distressed. To address this dementia care gap, we describe a Phase III efficacy trial testing an online platform, WeCareAdvisor, and design modifications necessitated by COVID-19. WeCareAdvisor provides caregivers with disease inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…While several technology-based non-pharmacological interventions geared toward helping caregivers manage neuropsychiatric symptoms in dementia exist (e.g. Gitlin et al, 2021), these programs have not been implemented on a larger scale, and they do not appear to specifically target behavioral disinhibition. As access to technology increases for people living with dementia and their family caregivers, the potential role of supportive technology-based intervention strategies deserves more attention.…”
Section: "Pharmacologicalmentioning
confidence: 99%
“…While several technology-based non-pharmacological interventions geared toward helping caregivers manage neuropsychiatric symptoms in dementia exist (e.g. Gitlin et al, 2021), these programs have not been implemented on a larger scale, and they do not appear to specifically target behavioral disinhibition. As access to technology increases for people living with dementia and their family caregivers, the potential role of supportive technology-based intervention strategies deserves more attention.…”
Section: "Pharmacologicalmentioning
confidence: 99%
“… 6 However, there is no approved disease-modifying medication for dementia, 7 8 and literature supports that BPSD is mostly undertreated. 9 Moreover, a lack of evidence has been shown concerning medication effectiveness in managing BPSD. 6 Consequently, BPSD negatively affects people with dementia psychologically, socially, and financially.…”
Section: Introductionmentioning
confidence: 99%
“…The management strategies, including the management of BPSD, include both pharmacological and non-pharmacological treatments 6. However, there is no approved disease-modifying medication for dementia,7 8 and literature supports that BPSD is mostly undertreated 9. Moreover, a lack of evidence has been shown concerning medication effectiveness in managing BPSD 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-help interventions have been conducted among dementia caregivers in several international settings, including the United States [ 7 ] and the Netherlands [ 8 ]. A published review reported that self-help interventions adopting cognitive behavioral therapy techniques could modify the caregivers’ thoughts and behaviors by facilitating self-help [ 9 ].…”
Section: Introductionmentioning
confidence: 99%